Pendampingan Juru Bahasa Inggris Dalam Mendukung Percepatan dan Akurasi Proses Pemeriksaan di Gakkum Ditpolairud Polda Kepri - Frangky Silitonga; Marthin Edi Candra Simarmata; Haerul Umami; Nurtjahyono Nurtjahyono; Dwi Joko Siswanto; Fierman Sjafirial Agustus (JURNAL NAGARA BHAKTI, 2026)
The Riau Islands area as an international border area has a high intensity of marine activities, so it is prone to various forms of law violations. The Riau Islands Marine Police (Ditpolairud Polda Kepri) as a law enforcement institution in the waters often handles cases involving foreign citizens. One of the main obstacles in the examination process is the language difference. Therefore, the assistance of an English interpreter is an important factor in speeding up and smoothing the examination process. This service activity aims to increase the capacity of interpreters and Gakkum Ditpolairud Polda Kepri personnel in supporting the effectiveness of case investigations. The methods used include training, direct assistance, case simulation, and evaluation. The results of the activity showed that the assistance of interpreters was able to increase the efficiency of examination time, improve the quality of examination minutes, and strengthen the juridical aspect of the case. This activity makes a real contribution to the professionalism and accountability of law enforcement in the Riau Islands Marine Police